Impact of Online Learning on the Environmental Awareness: An Opinions of Secondary School Teachers - Iscioglu, Ersun; Iscioglu, Deniz (Bucharest University Press, 2018)
The aim of this study is to inquire the effect of online learning on secondary school teachers' on the environmental awareness. Within this scope, the effect of online learning on teachers' environmental awareness and the effectiveness of the environment were assessed within the framework of teacher opinions. The study was designed as a qualitative research. The data were collected by means of the focus group interview method conducted as a result of the study. The working group of the study is composed of a total 42 secondary school teachers working in two different secondary schools located at Famagusta, N. Cyprus. Data gathered as a result of the study was analysed with descriptive analysis. According to the findings, discussions and suggestions are provided at the end of the study.
13th International Conference on Virtual Learning (ICVL 2018) -- OCT 26-27, 2018 -- December 1st 1918 Univ Alba Iulia, Alba Iulla, ROMANIA
Keywords: Online Learning Environment; Environmental Awareness; Secondary School Teachers